Spatial patterns of encroaching shrub species under different grazing regimes in a semi-arid savanna, eastern Karoo, South Africa. Issue 2 (8th July 2016) - Mureva, Admore; Ward, David
Abstract : Woody plant encroachment is increasing in arid and semi-arid regions of the world. We investigated the structure and fine-scale spatial pattern of encroaching species and how these patterns vary with different grazing regimes in semi-arid regions. In this study, we investigated how four encroaching shrub species ( Searsia erosa, S. burchellii, Diospyros lycioides and Eriocephalus ericoides ) in Middelburg (Eastern Cape, South Africa) coexist and partition space under different grazing regimes (viz. continuous rest, and continuous, summer and winter grazing). We used point-pattern analysis to assess the spatial ecology of these species. We also used an index of integration (mingling index), where low values indicate that they are surrounded by conspecifics and high values indicate that they are surrounded by heterospecifics. The three shrub species were highly mingled except in the winter-grazing plot, where S. burchellii and D. lycioides clustered. We found that the shrub species were generally aggregated in most of the grazing plots. These findings indicate that (1) at a fine spatial scale, grazing in the wet season promotes shrub encroachment, and (2) there is a tendency to aggregation among encroaching shrub species in the grazing plots.